Shipwreck 5 from Thonis–Heracleion, Egypt - Belov, Alexander; Goddio, Franck (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
The site of Thonis–Heracleion located in the Nile’s Delta contains more than a hundred ancient shipwrecks, most of which date to the Egyptian Late (664–332 BC) and Ptolemaic (332–31 BC) periods. Shipwreck 5 was excavated by the Institut Européen d’Archéologie Sous–Marine (IEASM) in 2019 and dates from the first half to the middle of the 4th century BC. The ship caught fire and sank during a putative naval battle. The preserved portion of the hull measures seven by three meters while the original length of the ship may be estimated at 14 to 15 m. The hull’s remains were in a good state of preservation and contained a considerable amount of thick ropes.